2016
DOI: 10.1021/acsami.6b05588
|View full text |Cite
|
Sign up to set email alerts
|

Tunable High-Field Magnetization in Strongly Exchange-Coupled Freestanding Co/CoO Core/Shell Coaxial Nanowires

Abstract: The exchange bias properties of Co/CoO coaxial core/shell nanowires have been investigated with cooling and applied fields perpendicular to the wire axis. This configuration leads to unexpected exchange-bias effects. Firstly, the magnetization value at high fields is found to depend on the field-cooling conditions. This effect arises from the competition between the magnetic anisotropy and the Zeeman energies for cooling fields perpendicular to the wire axis. This allows imprinting pre-defined magnetization st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 76 publications
0
19
0
1
Order By: Relevance
“…A usual approach in nanoscience generally involves two steps: first, the fabrication and characterization of nanomaterials, and second, employing their properties for the development of novel devices and widespread applications. In recent years, the fabrication and critical characterization of core-shell nanostructures has attracted enormous attention because of their widespread applications [ 1 , 2 , 3 , 4 , 5 ]. The enormous progress made in the field of high-density recording and nanotechnology make the study of exchange bias (EB) ferromagnetic (FM)/Antiferromagnetic (AF) core/shell system important.…”
Section: Introductionmentioning
confidence: 99%
“…A usual approach in nanoscience generally involves two steps: first, the fabrication and characterization of nanomaterials, and second, employing their properties for the development of novel devices and widespread applications. In recent years, the fabrication and critical characterization of core-shell nanostructures has attracted enormous attention because of their widespread applications [ 1 , 2 , 3 , 4 , 5 ]. The enormous progress made in the field of high-density recording and nanotechnology make the study of exchange bias (EB) ferromagnetic (FM)/Antiferromagnetic (AF) core/shell system important.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies, demonstrated exchange bias behavior in cylindrical permalloy nanowires [17], oxidized Co nanowires [18] and nanotubes [19] with characteristic accompanying effects, such as loop shift and training effect, previously reported for exchange-biased nanoparticles [16]. The competition between shape anisotropy, cooling field and applied field directions was shown to lead to a variety of novel properties of core-shell Co/CoO nanowires, such as, tailor-made magnetic response [20] and high-field irreversibility accompanied by cooling-field dependent magnetization [21]. Furthermore, Maurer et al [18] compared the hysteresis properties of cylindrical Co and Co/CoO nanowires and demonstrated the suppression of the coercive field due to surface oxidation as well as an anomalous temperature dependence, which they attributed to the thermal fluctuations of the oxide shell.…”
Section: Introductionmentioning
confidence: 99%
“…This latter finding is anticipated to have implications in the choice of nanowire diameters for tailoring the character of the DW as in diameter modulated nanowires [12,27]. Finally, we mention additional microstructural factors, such as core polycrystallinity, measurement conditions, such as the applied field direction [28], or sample conditions, such as the nanowire density and the concomitant inter-wire magnetostatic interactions, which are anticipated to modify the exchange biasing behavior of FM/AF core/shell nanowires. Detailed modeling in these directions is definitely highly required.…”
Section: Discussionmentioning
confidence: 94%